2012
DOI: 10.1128/jvi.05784-11
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Norovirus 1 Utilizes the Cytoskeleton Network To Establish Localization of the Replication Complex Proximal to the Microtubule Organizing Center

Abstract: Human noroviruses (family Caliciviridae) are the leading cause of nonbacterial gastroenteritis worldwide. Although Human noroviruses are significant enteric pathogens, there exists no reliable vaccine or therapy to treat infected individuals. To date, attempts to cultivate Human noroviruses within the laboratory have met with little success; however, the related murine norovirus mouse norovirus 1 (MNV-1) has provided an ideal model system to study norovirus replication due to the ease with which the virus is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 56 publications
10
44
0
Order By: Relevance
“…As previously reported (30), NS4-FLAG colocalized with NS7 in dense perinuclear foci (Fig. 8), in a position most likely consistent with the microtubule-organizing center, which has recently been reported to be the location for the replication complex (29). NS7 also appeared to show some diffuse staining throughout the cytoplasm of all infected cells, as has previously been observed (30).…”
Section: Figsupporting
confidence: 63%
“…As previously reported (30), NS4-FLAG colocalized with NS7 in dense perinuclear foci (Fig. 8), in a position most likely consistent with the microtubule-organizing center, which has recently been reported to be the location for the replication complex (29). NS7 also appeared to show some diffuse staining throughout the cytoplasm of all infected cells, as has previously been observed (30).…”
Section: Figsupporting
confidence: 63%
“…To date, a direct nucleic acidbinding activity of Talin-1 has not been reported; however, this protein has been found associated with a number of nucleic acidbinding proteins also identified in this study, namely, YBX1, FUS, hnRNPK, hnRNP E1 (PCBP1), and PABP (13). Recent studies indicated that MNV replication requires components of the cytoskeleton network for correct localization of the viral replication complex (29). Further studies to dissect a possible role for Talin-1 in the norovirus life cycle are under way.…”
Section: Figmentioning
confidence: 91%
“…Tubulin acetylation is such a modification that is involved in the replication process of several viruses, including herpes simplex virus 1 (HSV-1) [81], mouse norovirus 1 [82] and adenovirus [83]. Besides, tubulin acetylation is supposed to guide and accelerate the nuclear trafficking of post-entry viruses, and inhibition of HDAC6 by its specific inhibitors could apparently improve the replication efficiency of oncolytic viruses [84,85].…”
Section: Replicationmentioning
confidence: 99%